2008
DOI: 10.1162/pres.17.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Use of Simulated Thermal Cues for Material Discrimination and Identification with a Multi-Fingered Display

Abstract: Thermal cues provide information about the thermal properties of an object held in the hand. These cues can be simulated in a thermal display and used to assist in identifying the object. Two experiments were conducted using a thermal display that simulated the cues associated with contact with different materials. The thermal contact model was based on a semi-infinite body model that included thermal contact resistance and blood perfusion. Its performance was evaluated in two experiments, the first of which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
(43 reference statements)
0
25
1
Order By: Relevance
“…Indeed, changing the size of a thermal stimulus drastically affects the perceived intensity. This property is especially important in warmth perception in which intensity and spatial extent of the stimulus have equal influence on the perceived intensity [12,22]. Unpublished preliminary data from our lab suggested that the spatial extent of thermal stimulation more strongly affects perceptual decision making in blind compared to sighted participants.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Indeed, changing the size of a thermal stimulus drastically affects the perceived intensity. This property is especially important in warmth perception in which intensity and spatial extent of the stimulus have equal influence on the perceived intensity [12,22]. Unpublished preliminary data from our lab suggested that the spatial extent of thermal stimulation more strongly affects perceptual decision making in blind compared to sighted participants.…”
Section: Introductionmentioning
confidence: 88%
“…It has been shown that people can discriminate between a broad range of materials by relying solely on thermal diffusivity properties [11][12][13]. Because of their lack of vision, blind individuals might http://dx.doi.org/10.1016/j.bbr.2015.01.037 0166-4328/© 2015 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current models have considered the effects of blood perfusion and the thermal and mechanical properties of the skin and contact material (Bergamasco et al, 1997;Citerin et al, 2006;Deml et al, 2006;Ho & Jones 2006a;Yamamoto et al, 2004;Yang et al 2008). Ho and Jones (2006a) where the ratio of contact pressure to microhardness is 1E-6 to 2E-2.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal models are developed that capture the responses of the skin on contact with different materials (e.g., ceramic, plastic, aluminum) and the models are then implemented in a thermal display typically consisting of thermoelectric coolers, thermal sensors, and a temperature control system (Bergamasco, Alessi, & Calcara, 1997;Ho & Jones, 2007). The results from studies on virtual object recognition using thermal cues indicate that model-based displays are able to present cues that can be used effectively to identify and discriminate between materials and that performance on these tasks is comparable to that achieved with real materials (Ho & Jones, 2007;Yang, Jones, & Kwon, 2008).…”
mentioning
confidence: 99%